Human bronchus and intestine express the same mucin gene. - Jany, B H (1991)
The amino acid and sugar composition of mucins from various organs is similar but not identical. This could arise by one or more of the following: organ-specific processing of a single core protein, organ-specific splicing of a single mucin mRNA, or organ-specific expression of various mucin genes. To begin to investigate the source of this variability, we examined (a) immunological cross-reactivity and (b) cDNA cross-hybridization, among several mucin-secreting organs of the human body. Peptide-directed antibodies raised against both nondeglycosylated (LS) and deglycosylated (HFB) intestinal mucin strongly stained mucous cells in the bronchial epithelium and submucosal glands, indicating homology between mucins of the bronchus and intestine at the peptide level. By screening a bronchus cDNA library with an intestinal mucin cDNA, SMUC-41, we isolated a bronchus mucin cDNA, HAM-1. This cDNA is 96% homologous to the first repeat of SMUC-41. HAM-1 hybridized to restriction fragments of human genomic DNA identical to those hybridizing to SMUC-41 on Southern blots. SMUC-41 also hybridized to polydisperse transcripts in the bronchus, cervix, gall bladder, and mammary gland, indicating mucin homology among all these organs at the RNA level. We conclude that the bronchus and intestine express a common mucin gene, which is likely co-expressed by at least several other mucin-secreting organs.